ChemInform Abstract: NHC—Copper Hydrides as Chemoselective Reducing Agents: Catalytic Reduction of Alkynes, Alkyl Triflates, and Alkyl Halides. Issue 44 (4th November 2014) - Cox, Nick; Dang, Hester; Whittaker, Aaron M.; Lalic, Gojko
Abstract Highly chemoselective NHC—copper‐catalyzed reductions of unactivated terminal and internal alkynes, as well as of primary alkyl triflates and primary and secondary alkyl halides are described.